Pemanfaatan Ekstrak Bawang Putih (Allium sativum L.) sebagai Desinfektan untuk Menurunkan Angka Kuman Dinding di Ruang Laboratorium - Tri Wiji Wastiti; Sri Muryani; Indah Werdiningsih (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
The measurement of wall microbe number in the laboratories of Environmental Health Department of The Polytechnic of Health of Yogyakarta was 70,9 CFU/cm2, which did not comply with the quality standard regulated by The Ministry of Health’s decree No. 1204/Menkes/SK/X/2004 about Health Requirement for Hospitals, i.e. 0-5 CFU/cm2. One of the efforts that need to be applied is disinfecting the laboratories’ rooms. The study was aimed to know whether 20 % concentration garlic extract is able to reduce the germ numbers of the walls. This study was a pretest post-test designed experiment. The sample were taken at five different laboratories, and for each laboratory there were four sampling points. The sampling technique used sterile cotton stick that were swabbed on a 10 cm x 10 cm wall surface and then were dipped into 10 ml PBS.The result showed that garlic extract with 20 % concentration can decrease the germ number ofwalls to 32,35 CFU/cm2, or in average of 38,6 CFU/cm2 (54,4 %).